A systematic exploration of ginsenoside Rg5 reveals anti-inflammatory functions in airway mucosa cells - Heo, Hyojin; Kim, Yumin; Cha, Byungsun; Brito, Sofia; Kim, Haneul; Kim, Hyunjin; Fatombi, Bassiratou M.; Jung, So Young; Lee, So Min; Lei, Lei; Lee, Sang Hun; Park, Geon woo; et al. (Journal of Ginseng Research, 2023)
Background: Hyperactivated airway mucosa cells overproduce mucin and cause severe breathing complications. Here, we aimed to identify the effects of saponins derived from Panax ginseng on inflammation and mucin overproduction. Methods: NCI–H292 cells were pre-incubated with 16 saponins derived from P. ginseng, and mucin overproduction was induced by treatment with phorbol 12-myristate 13-acetate (PMA). Mucin protein MUC5AC was quantified by enzyme-linked immunosorbent assay, and mRNA levels were analyzed using quantitative polymerase chain reaction (qPCR). Moreover, we performed a transcriptome analysis of PMA-treated NCI–H292 cells in the absence or presence of Rg5, and differential gene expression was confirmed using qPCR. Phosphorylation levels of signaling molecules, and the abundance of lipid droplets, were measured by western blotting, flow cytometry, and confocal microscopy. Results: Ginsenoside Rg5 effectively reduced MUC5AC secretion and decreased MUC5AC mRNA levels. A systematic functional network analysis revealed that Rg5 upregulated cholesterol and glycerolipid metabolism, resulting in the production of lipid droplets to clear reactive oxygen species (ROS), and modulated the mitogen-activated protein kinase and nuclear factor (NF)-κB signaling pathways to regulate inflammatory responses. Rg5 induced the accumulation of lipid droplets and decreased cellular ROS levels, and N-acetyl-L-cysteine, a ROS inhibitor, reduced MUC5AC secretion via Rg5. Furthermore, Rg5 hampered the phosphorylation of extracellular signal-regulated kinase and p38 proteins, affecting the NF-κB signaling pathway and pro-inflammatory responses. Conclusion: Rg5 alleviated inflammatory responses by reducing mucin secretion and promoting lipid droplet-mediated ROS clearance. Therefore, Rg5 may have potential as a therapeutic agent to alleviate respiratory disorders caused by hyperactivation of mucosa cells.
Keywords: Airway mucosa inflammation; Ginsenoside Rg5; Lipid droplet; Mucin overproduction; Reactive oxygen species